PENGARUH MULTIMEDIA INTERAKTIF BERBASIS PROBLEM-BASED LEARNING TERHADAP HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA SD: STUDI LITERATUR - Nita Khusnun Nandifa; Fathur Rokhman; Agung Tri Prasetya; Decky Avrilianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examined the effect of interactive multimedia integrated with Problem-Based Learning on elementary students’ learning outcomes and critical thinking skills. A systematic literature review was conducted on empirical studies published between 2023 and 2025 using structured selection and qualitative synthesis. A total of 15 selected articles were analyzed. The findings showed that this integration improved academic achievement and enhanced critical thinking, particularly in analysis, evaluation, and problem-solving. The positive effects appeared consistently across learning contexts, especially in science and thematic subjects. Interactive multimedia supported active engagement and deeper understanding. Overall, the results confirmed that combining interactive media with problem-based approaches effectively strengthened cognitive outcomes and higher-order thinking in elementary education.